SCREENING FINGER MILLET GENOTYPES FOR RESISTANCE TO FOOT-ROT AND SMUT* - AND T. B. ANILKUMAR, Y. M. SOMASEKHARA, S. VISWANATH (Indian Phytopathology, 2002)
Seventeen finger millet (Eleusine coracana Gaertn.) genotypes were screened under field and glasshouse conditions for their reactions to foot-rot caused by Sclerotium rolfsii. Genotype I8IE had the least incidence (5.2 per cent) under natural conditions in field and 11.9 per cent when inoculated artificially in glasshouse as against 44.7 and 77.9 per cent incidence on Puma, a susceptible check cultivar under similar conditions. The visual rating on a 0 to 4 scale was also the least (0.78) on I8IE. The area under disease progress curve values for I8IE was only 15.75 as against 92.1 on HR I8IE 13-1. These genotypes were also screened for their reaction to smut, caused by Melanopsichium eleusinis under field conditions. Puma recorded the highest incidence (72.2 per cent) and IE 1012 and GE 162 the least incidence, viz., 6.6 and 9.2 per cent respectively. These results indicate the existence of partial resistance to foot- rot and smut incidence.